Role of ENSO on Conflicts in the Global South - Roy, Shouraseni Sen (Frontiers in Climate, 2022)
In recent years, there has been increasing research on the impact of climate change related processes on the occurrence of conflicts in different parts of the world. Analysis of conflicts over extended time periods indicate the possible role of climate change and climate variability on the occurrence of conflicts, particularly in the tropics. With the recent release of the UCDP georeferenced dataset on specific locations of conflicts between 1989 and 2014, we can now examine the temporal patterns of conflicts at a finer spatial resolution. In this study, the role of El Niño-Southern Oscillation (ENSO) on the spatio-temporal patterns of conflicts has been analyzed by using a variety of geospatial analysis techniques. The results of the analysis reveal that there were a greater number of conflicts during El Niño years at both the global and continental scale (except North America). In addition, the spatial patterns of conflicts showed greater concentration of intensifying and consecutive hot spots in South and Southeast Asia, the Middle East, and Central and Eastern Africa during El Niño years versus La Niña years. Specifically, intensifying hot spots of conflicts overlapped with the relatively arid and semi-arid areas of the Global South.